A Rare Complication of Corneal Abrasion in Otorhinolaryngology Procedure: Lessons Learnt (Bangladesh Journal of Medical Science, 2012)
Despite their close anatomical relationship, orbital complications rarely occur during otorhinolaryngology operations. The well-known complication is the orbital injury during endoscopic sinus surgery. Procedures such as tonsillectomy or sinus surgery limited to the ostium widening rarely induce such an injury. We report two cases of corneal abrasion after otorhinolaryngological operative procedures. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9826 BJMS 2012; 11(1): 61-62